فعالية واسطة التعليم تدوير (Spinner) لإتقان الإعراب في مادة النحو للفصل الثامن بمعهد السلام العصري الإسلامي سوكوهارجو - الفي ممدوح نورالدين; نوال فجريا الحق; أكوس يس (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research is an experimental research with a type of quasi-experiment with a pretest-posttest non-equivalent control group research design. This study consists of the dependent variable, namely mastery of I'rab nawhu and the independent variable, namely spinner learning media. The samples of this study were 26 students of class 8D as the control class and 25 students of class 8F as the experimental class. The instruments used are tests and documentation. The data analysis technique used is descriptive statistics and inferential analysis on the Wilcoxon test. The media chosen in this study is spinner learning media for mastery of I'rab of students in class 8F PPMI Assalam. In this study, the average pre-test score was 54% and the average post-test score rose to 78%, with an increase of 24%. However, the hypothesis test obtained a value of 0.000 which is greater than 0.05 which means H0 is rejected and Ha is accepted.